2009
DOI: 10.3382/ps.2008-00177
|View full text |Cite
|
Sign up to set email alerts
|

The effect of light intensity on the behavior, eye and leg health, and immune function of broiler chickens

Abstract: Broilers are typically raised commercially in dim lighting. It has been suggested that providing brighter light intensity could improve health and provide opportunities for more normal behavioral rhythms. We examined the effects of 3 photophase light intensities (5, 50, and 200 lx) on activity patterns, immune function, and eye and leg condition of broilers (n = 753; 6 replicate pens/treatment). Broilers were reared with one of these intensities from 1 to 6 wk of age; photoperiod consisted of 16L:8D with 1 lx … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
104
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(114 citation statements)
references
References 35 publications
9
104
0
1
Order By: Relevance
“…At the same time, some studies showed that birds reared in low light intensity at 0.5 or 1 lux resulted in heavier and larger eyes (Deep et al, 2010). Blatchford et al (2009) reported that broilers had heavier and lager eyes at 5 lux, whereas Olanrewaju et al (2012) and Deep et al (2013) found no difference in eye size under 5 lux as compared to birds under higher light intensities. These studies used different light intensities (range from 0.1 to 220 lux), strains (laying hens, turkeys and broilers) and ages (from day-old to 46-week-old), making it difficult to draw concrete conclusions.…”
Section: Daily Time Spentmentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, some studies showed that birds reared in low light intensity at 0.5 or 1 lux resulted in heavier and larger eyes (Deep et al, 2010). Blatchford et al (2009) reported that broilers had heavier and lager eyes at 5 lux, whereas Olanrewaju et al (2012) and Deep et al (2013) found no difference in eye size under 5 lux as compared to birds under higher light intensities. These studies used different light intensities (range from 0.1 to 220 lux), strains (laying hens, turkeys and broilers) and ages (from day-old to 46-week-old), making it difficult to draw concrete conclusions.…”
Section: Daily Time Spentmentioning
confidence: 99%
“…However, improper low light intensity (e.g. 1.1 lux) could cause issues for broilers such as adrenal overweight (Siopes et al, 1984), body underweight (Hester et al, 1987), leg problems (Hester et al, 1985;Deep et al, 2010), and partial or complete blindness due to eye morphology change (Blatchford et al, 2009;Deep et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Kristensen et al [10] , Blatchford et al [12] , Deep et al [1] , Ahmad et al [2] reported that light intensity has no significant effects on BW at market age. Newberry et al [26] also found no influence between light intensity groups (180 and 6 lux) on BW.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of light intensity (ranging from 1 to 150 lx) on body weight (BW), FC, feed conversion ratio (FCR) and mortality in broiler chickens was reported as statistically nonsignificant by some studies [10][11][12] . Processed fillet weights were reported to be higher in 1.08 lux light intensity (dim light) than those kept in 161.4 lux light intensity (bright light) [13] .…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to an extended lighting period or to continuous illumination has been shown to decrease both humoral and cell-mediated immunity in avian species, exemplified by the broiler chicken (Kirby and Froman, 1991) and Japanese quail (Moore and Siopes, 2000). These effects may be due to seasonal changes in the blood melatonin concentration (Kliger et al, 2000), since light intensity itself did not affect immune parameters like B-and T-lymphocyte proliferation, plasma lysozyme concentration or the bacterial killing ability of whole blood (Blatchford et al, 2009).…”
Section: Introductionmentioning
confidence: 99%